Prevalence and Determinants of Complete Postnatal Care Service Utilization in Northern Shoa, Ethiopia. (14th August 2018) - Akibu, Mohammed; Tsegaye, Wintana; Megersa, Tewodros; Nurgi, Sodere
Abstract : Background . Postnatal period presents the highest risk of death for mothers and newborns. Although progress has been made in expanding the coverage for most of maternal health services, national prevalence of postnatal care service utilization in Ethiopia is still extremely limited. Hence, this study aims to determine the prevalence and factors associated with complete postnatal care service utilization in Northern Shoa, Ethiopia. Methods . Community based cross-sectional survey was conducted between November 2016 and February 2017. A total of 510 mothers were included in the study using multistage sampling technique. The data were collected through face-to-face interview. Bivariate and multivariate logistic regression models were fitted to identify factors associated with complete postnatal care utilization at p value of < 0.05. SPSS version 20 was used to analyze the data. Results . The prevalence of complete postnatal care utilization was found to be 28.4% in the study area. Mode of delivery (AOR=5.7, 95% CI = 3.9, 19), number of children (AOR= 2.5 95% CI, 1.4, 14.2), and level of education (AOR=3.2 95% CI, 1.1, 9.2) were the factors statistically associated with complete postnatal service uptake. Being healthy was the major (48.8%) reason mentioned for not complying with the recommended three postnatal visits. Conclusion . The prevalence of complete postnatal care service in the study area was found to be low, and it is far less than the targeted zonal and regional plan. Reinforcing the existing policies and strategies to increase women level of awareness about postnatal care and intensive counseling during antenatal care and delivery are the recommendations based upon the current finding.